2019
DOI: 10.1007/s00167-019-05709-7
|View full text |Cite
|
Sign up to set email alerts
|

Flexible reamers create comparable anterior cruciate ligament reconstruction femoral tunnels without the hyperflexion required with rigid reamers: 3D-CT analysis of tunnel morphology in a randomised clinical trial

Abstract: Purpose The hyperflexion required for femoral tunnel drilling in anterior cruciate ligament reconstruction can be challenging in patients with increased body habitus or musculature. Whilst allowing femoral tunnel creation without hyperflexion, additional benefits of flexible reamers have been proposed in terms of tunnel dimensions. The purpose of this study was to examine whether these theoretical benefits are seen in a clinical study. Methods Fifty adult patients (with isolated anterior cruciate ligament rupt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Eight included studies 9 , 15 , 16 , 20 , 21 , 23 , 33 , 35 quantified femoral tunnel positioning by utilizing radiologic parameters. No studies reported any significant difference in the intra-articular femoral tunnel aperture location.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eight included studies 9 , 15 , 16 , 20 , 21 , 23 , 33 , 35 quantified femoral tunnel positioning by utilizing radiologic parameters. No studies reported any significant difference in the intra-articular femoral tunnel aperture location.…”
Section: Resultsmentioning
confidence: 99%
“…No studies reported any significant difference in the intra-articular femoral tunnel aperture location. 15 , 16 , 20 , 36 Table 3 illustrates a comparison of 6 studies that reported femoral tunnel positioning in the frontal, coronal, sagittal, or axial plane. 15 , 20 , 21 , 23 , 33 , 35 Two out of 3 studies 15 , 33 , 35 reported a significant difference in tunnel positioning in the sagittal plane, with AM-FR resulting in greater tunnel anteversion in these studies ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients were recruited as part of a published study comparing flexible and rigid femoral tunnel reamers [6]. Ethical review board approval was additionally received, prior to study commencement, for the present analysis (study number 16/SW/0080).…”
Section: Methodsmentioning
confidence: 99%